2010
DOI: 10.3109/00016489.2010.541937
|View full text |Cite
|
Sign up to set email alerts
|

Electroporation therapy for T1 and T2 oral tongue cancer

Abstract: No local recurrence was recorded in any patient during the follow-up. Three patients died, two from progressive regional disease. Of the 12 surviving patients, 2 patients had regional recurrence and 10 patients including the 5 patients treated with EPT alone were tumor-free both locally and regionally at the last follow-up. The functional outcome for speech and eating were very good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…The mucosal reaction to electrochemotherapy differs from cutaneous electrochemotherapy. Previous publications have reported this reaction and our experience concurs with this (Figure ). Primarily, a swelling phase occurs.…”
Section: Resultssupporting
confidence: 92%
“…The mucosal reaction to electrochemotherapy differs from cutaneous electrochemotherapy. Previous publications have reported this reaction and our experience concurs with this (Figure ). Primarily, a swelling phase occurs.…”
Section: Resultssupporting
confidence: 92%
“…The overall appearance of the post-treatment mucosal reaction to calcium electroporation with swelling and necrosis was similar to the one shown with electrochemotherapy. 10,12 Regarding tumor response, a recent trial using electrochemotherapy on 43 patients showed an objective response rate (CR + PR) of 56% with complete response in 19%. 14 Currently, we cannot compare tumor responses between these two electroporation modalities since the calcium data is based on only six patients.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Currently, electroporation is clinically used in combination with chemotherapy, termed electrochemotherapy (ECT). ECT is mainly used on skin tumors and metastases [6][7][8][9] but several studies [10][11][12][13] including a recently published multi-institutional trial 14 have shown that the treatment also can be applied on mucosal head and neck cancers with good tumor response.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally subsequent studies 11,49,66,[89][90][91][92] of ECT evaluating its effect in the treatment of melanoma and other skin cancers continue to demonstrate the efficacy of the treatment, with response rates comparable to the earlier studies, ranging from 46-100%. Repeated treatments are feasible as demonstrated by Campana et al 90 and Quaglino et al 11 producing additional clinical responses in patients who had initial non or partial responses or who presented with new recurrent lesions.…”
Section: Wwwintechopencommentioning
confidence: 76%